1984
DOI: 10.1002/1097-0142(19840101)53:1<1::aid-cncr2820530102>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of prolonged intermittent therapy with combined 5-fluorouracil and methyl-ccnu following resection for carcinoma of the large bowel. A veterans administration surgical oncology group report

Abstract: This prospective evaluation of 5‐FU and methyl‐CCNU administered in combination to patients with curative surgery for histologically proved colorectal adenocarcinoma is based upon 645 patients randomized between August 1973 and July 1979. Beyond the requirement that the resection be clinically and microscopically complete, patients were not stratified prior to random treatment assignment to surgery alone or surgery followed by adjuvant chemotherapy. Drug therapy consisted of discrete 5‐day courses administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

1985
1985
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…Older trials of adjuvant chemotherapy using fluorouracil alone or combined with semustine, failed to show a significant improvement in either overall or disease-free survival for patients receiving treatment compared with concurrently randomized control patients receiving no adjuvant therapy [85][86][87][88].…”
Section: Overall Treatment Strategymentioning
confidence: 99%
“…Older trials of adjuvant chemotherapy using fluorouracil alone or combined with semustine, failed to show a significant improvement in either overall or disease-free survival for patients receiving treatment compared with concurrently randomized control patients receiving no adjuvant therapy [85][86][87][88].…”
Section: Overall Treatment Strategymentioning
confidence: 99%
“…After a median 4-year follow-up, a significant (P<0.03) survival benefit was reported for treated patients. However, subsequent randomized trials of these agents by the Veterans Administration Surgical Oncology Study Group and the Eastern Cooperative Oncology Group showed no survival advantage for this adjuvant therapy compared with surgery alone [22,23].…”
Section: Combination Chemotherapymentioning
confidence: 99%
“…The Veterans Administration Surgical Oncology Group compared 5-FU and methyl-CCNU to observation and failed to demonstrate any treatment advantage [4]. Results with bacille Calmette-Guérin (BCG) in animal tumor model systems prompted a trial by the Gastrointestinal Tumor Study Group (GITSG), in which 621 patients with Dukes' stage B2 and C disease were randomized postoperatively to observation or therapy with methyl-CCNU and 5-FU, BCG, or a combination of BCG and chemotherapy.…”
Section: Clinical Trials Of Adjuvant Chemotherapymentioning
confidence: 99%